Analisis Penjadwalan Dan Pengendalian Proyek Dengan Precedence Diagram Method (PDM) (Studi Kasus di Pekerjaan Peningkatan Jalan Jagabaya-Nagarapageuh Kecamatan Panawangan Kabupaten Ciamis) - sumarno, wahyu; farha, aulia; defiana, yanti (Jurnal Ilmiah Teknik Sipil, 2023)
In its development, construction project work is currently becoming more complex and more sophisticated. The implementation of construction projects now uses a lot of new technology, more and more human and material resources, and large funds. Therefore, the implementation of construction projects requires methods that can accommodate the arrangement of various elements in the construction project. One of them is job scheduling method. This research was carried out with the aim of knowing the Scheduling and Time Control of the Jagabaya-Nagarapageuh Road Improvement Project with the Precedence Diagram Method (PDM). This study uses data collection methods. With this data will be analyzed Scheduling and Control using the Precedence Diagram Method (PDM). Based on the results of the study, it was found that the work time was faster and more efficient which was initially for 150 days, if using the Precedence Diagram Method (PDM) method it could be completed for 122 working days. Then there is an acceleration of the duration of the work as much as 28 working days.